IMPROVING STUDENTSâ€™ VOCABULARY ABILITY BY USING GUIDED DISCOVERY METHOD AT THE SECOND GRADE STUDENTS OF SMP NEGERI 1 TAKKALALLA WAJO - Bustang, Bustang (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The purpose of this research was to improve the studentsâ€™ vocabulary Ability by using Guided Discovery method at the second-grade students of SMP Negeri 1 Takkalalla Wajo The question of this research was â€œHow to improve the studentsâ€™ vocabulary Ability at the second-grade students of SMP Negeri 1 Takkalalla Wajo in each cycle and every meeting by using the Guided Discovery Method?â€. The objective of this research was to improve the studentsâ€™ vocabulary Ability at the second-grade students of SMP Negeri 1 Takkalalla Wajo in each cycle and every meeting by using the Guided Discovery Method. The significance of the research was the result of this research became useful information, for both English teacher and the students to improve the vocabulary Ability by using Guided Discovery method. The scope of the research was focused on improving the students' vocabulary Ability at the second grade especially noun of common noun such as people, animals, places and things in the narrative text about fables, legends, and fairy tales stories. The design of the research was collaborative Classroom Action Research (CAR). It means that when implementing the research, the researcher collaborated by the English teacher of SMP Negeri 1 Takkalalla Wajo. The subject of this research was VII A class in academic year 2022/2023. The research was conducted in two cycles consisted of preliminary research, planning, implementing, observing and data analyzing and reflecting. The data of the research was obtained of result the vocabulary test and the observation sheet. Meanwhile in the form of product, the improvement could be examined of result the vocabulary test. In the first cycle, improvement obtained by three students with average score 54 (4,3%). While, the second cycle improvement obtained by all students with average score 84 (100%). It means that they had achieved the criteria of success in this research. That is 65 (80%).